Safeguarding Women's Rights and Heirship: An Evaluation of Mandatory Muslim Marriage Registration in Sri Lanka - Iqbal Saujan; Seeni Mohamed Mohamed Nafees; Iqbal Subhan Nugraha (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
Marriage registration serves as a pivotal legal mechanism for safeguarding the rights of spouses and heirs. In Sri Lanka, while marriage registration is obligatory for most communities, it remains optional for Muslims under the Muslim Marriage and Divorce Act (MMDA) of 1951. This study examines the necessity of mandatory Muslim marriage registration in Sri Lanka through the framework of Maqāṣid al-Sharīʿah. Utilizing legal analysis, this study assesses the impact of optional registration on women's rights and the legal status of heirs, highlighting challenges such as inheritance disputes, economic vulnerabilities, and child marriage. It also highlights the historical context of marriage registration in Sri Lanka, comparative practices in other Muslim-majority countries, and the perspectives of Islamic scholars on marriage registration. The findings emphasize the alignment of mandatory registration with the objectives of preserving lineage (ḥifẓ al-nasl), wealth (ḥifẓ al-māl), and dignity (ḥifẓ al-ʿird). The article concludes by proposing policy recommendations for legal reforms to the MMDA to mandate marriage registration, thereby enhancing the protection of the rights and well-being of the Muslim community in Sri Lanka.